Nutraceuticals: A Review of Their Therapeutic Benefits and Health Implications - Sakshi P. Waikar,; Tejaswini G. Khonde,; Nilakshi N. Dhoble,; Nitin Padole,; Pankaj Dhapke,; Jagdish Baheti, (Asian Journal of Pharmaceutical Research and Development, 2024)
Nutrition and medication are combined to form nutraceuticals was invented in 1989 to define materials that could be second hand as nutriments that have well-being paybacks. Widely construed, nutraceuticals are nutrients or components of nutrients that play a significant part in adapting to and maintaining the regular physiological functions necessary to maintain healthy human beings. Nutritional fibres, probiotics, prebiotics, polyunsaturated fatty acids, antioxidants, spices, phytochemicals and other diverse kinds of herbal/natural nutrients can all be categorised as nutrient items utilised in nutraceuticals. Healthcare branch focused on the all features about the nutraceuticals, ranging from systematic parts to medical trials, from efficiency studies to valuable effects on well-being status. Nutraceuticals describe themselves as a natural and essential component of our daily diet. These nutraceuticals aid in the fight against some of the most pressing health issues of the day, including obesity, heart disease, cancer, osteoporosis, arthritis, diabetes, and cholesterol. Herbal nutraceuticals are utilised as a potent weapon for maintaining health and fighting major, chronic diseases that are brought on by poor nutrition, thereby encouraging the best health, longevity, and quality of life.